GENETIC COLOR POLYMORPHISMS ON COMMON CARP STOCKS IN INDONESIA - Rudhy Gustiano (Research Center for Fisheries, 1999)
Common carp is the most important species of fish culture in Indonesia, especially in the island of Java, The objective ofthis study was to clarify the cellular basis ofcolor inheritanceamong body morphs of this fish.